Identification and validation of the phosphorylation sites on Aristaless-related homeobox protein. Issue 7 (15th July 2020) - Shi, Xiuyu; Lin, Wenbo; Gao, Xiang; Xie, Wen; Golden, Jeffrey A.; Tao, Tao
Abstract: The Aristaless-related homeobox protein (ARX) is a transcription factor expressed in the developing forebrain, skeletal muscle, pancreas, testis, and a variety of other tissues. It is known to have context-dependent transcriptional activator and repressor activity, although how it can achieve these opposing functions remains poorly understood. We hypothesized phosphorylation status might play a role in pivoting ARX between functioning as an activator or repressor. To gain further mechanistic insight as to how ARX functions, we identified multiple phosphorylation sites on ARX. We further established PKA as the kinase that phosphorylates ARX at least at Ser 266 in mice. Two other kinases, CK2α and CDK4/cyclin D1, were also identified as kinases that phosphorylate ARX in vitro . Unexpectedly, phosphorylation status did not change either the nuclear localization or transcriptional function of ARX.